I dreamed of falling : a novel - Dahl, Julia, 1977- (Minotaur Books, 2024)
"In acclaimed author Julia Dahl's new standalone, the death of a young mother triggers an avalanche of secrets in a small Hudson Valley town. Roman Grady is the sole reporter for the local newspaper in a tiny Hudson Valley town - a town so small that every store opening and DUI is considered newsworthy. But when Roman's longtime girlfriend, Ashley, the mother of his four-year-old son, is found dead, he realizes he had no idea what was really going on in her life. And when he starts asking questions, he's not prepared for the answers. What was Ashley doing at the cliffside home of her troubled ex-girlfriend? How did no one in a house full of people see what happened to her? And why does it seem like everyone in town suddenly has something to hide? As Roman and his mother dig into Ashley's last few months, the truths they uncover threaten to expose painful secrets. The kind of secrets that can get you killed. A gripping thriller and a moving portrait of a family struggling through tragedy, I Dreamed of Falling showcases Julia Dahl's talent for using crime fiction to tell an immersive and unforgettable story. Dahl's unflinching novel asks hard questions about love, regret, inequality, and the possibilities and the perils of forgiveness"--